Profil Juvana dan Pengurusan Pemulihan di Asrama Pokok Sena, Kedah - Kamal, Hj Ab Hamid (1998)
This study emphasizes on the Profile and Juvenile Rehabilitation management. The respondents were 20 juvenile delinquents of Pokok Sena Probation Hostel whom are under rehabilitation according to Juvenile Court Act 1947. The instruments used were interview and questionnaire which were given to the respondents using the ‘Non Probability Sampling’. This study was carried out to identify the profile of juvenile delinquents, causes of involvement and factors that encourages juvenile delinquency. The respondents’ personality, self-behaviour, perception, involvement and family background factors were also examined in order to know whether they play part in the scenario that occur. The responses from the questions and interviews have shown that lack of positive contribution from the respondents’ personal life, surroundings, environment, religious and academic education are the factors that restate them in the juvenile delinquency cases. Various ways and method have been utilized to prevent as well as minimized the juvenile delinquency problems including punishment to both delinquents and parents but the implementation does not prevail.